Exploration of Mother’s Perception of Toddlers About Stunting: Qualitative Study - Filia Sofiani Ikasari; Iis Pusparina; Fir'ad Setya Nugraha; Ahmad Rizqo Abdillah; Cut Ika Anugrah Kirana; Muhammad Wirandi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Stunting is a significant health issue in Southeast Asia, commonly resulting from chronic malnutrition. Mothers play a crucial role in their children’s growth, development, and stunting prevention. Perceptions shape maternal attitudes and behaviors, influencing care for toddlers. This study aims to explore mothers’ perceptions of stunting in the Martapura 1 Health Center work area Methods: A qualitative study with a descriptive phenomenological approach was conducted. Sixteen mothers of stunted toddlers were selected using purposive sampling. Data were collected through observation, interviews, documentation, and audio recordings. Ethical approval was obtained from the Health Research Ethics Commission of the Stikes Intan Martapura. Results: Five themes emerged regarding mothers' perceptions of stunting: Definition of Stunting: Mothers associated stunting with genetic conditions, malnutrition, underweight, short stature, stunted growth and small body size; Causes of Stunting: Perceptions included many factors, malnutrition, cultural beliefs like